1996
DOI: 10.1097/00006534-199606000-00032
|View full text |Cite
|
Sign up to set email alerts
|

Submucous Cleft Palate: Diagnostic Methods and Outcomes of Surgical Treatment

Abstract: The following statements summarize our interpretation of the literature regarding submucous cleft palate: Incidence and Diagnosis of Submucous Cleft Palate 1. In surveys of classic stigmata of submucous cleft palate among the general population, the incidence has been reported to be 0.02 to 0.08 percent. In the larger of these series, the incidence of velopharyngeal inadequacy among patients identified to have submucous cleft palate was 1 to 9. The incidence of occult submucous cleft palate is not known, since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
12

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 44 publications
3
96
0
12
Order By: Relevance
“…Several studies have shown that speech outcomes are affected by patient age at the time of surgery. 3,9,10 Unfortunately, submucous cleft palate is often identified late. McWilliams reported only 36% of patients with a submucous cleft palate were diagnosed by 4 years of age, and 24% were diagnosed between 8 and 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that speech outcomes are affected by patient age at the time of surgery. 3,9,10 Unfortunately, submucous cleft palate is often identified late. McWilliams reported only 36% of patients with a submucous cleft palate were diagnosed by 4 years of age, and 24% were diagnosed between 8 and 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…14 With the incidence of bifid uvula reported to be between 1% and 7.5%, this suggests that the incidence of occult submucous cleft palate may be higher than appreciated. 3 Another study compared a group of 25 children with an isolated cleft lip not extending into the secondary palate with a control group of 25 children without a known facial cleft. 7 No patients in the control group were identified to have submucous cleft palate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another dilemma in the reporting of OFCs is that some studies include all births in the rate calculations while others include only live births. Since clefts are more frequent among stillborn and spontaneously aborted infants, their inclusion in the denominator impact the results significantly [29][30][31]. The IPDTOC Working Group, 2011 have summarized the conclusions of all recent epidemiologic data on OFC as follows [32,33]:…”
Section: Midline Cleft Lipmentioning
confidence: 99%
“…A fenda submucosa de palato (FPSM), é um subgrupo de fendas labiopalatinas,que apresenta uma prevalência de 1:1250 -1:6000 (GOSAIN et al, 1996 VELASCO et al, 1988). A investigação auditiva deve ser realizada com triagem auditiva neonatal e com uma segunda triagem por volta dos cinco anos de idade (HABEL et al, 2014).…”
Section: Anomalias Palatinas E Da Cavidade Oralunclassified